2015
DOI: 10.1016/j.bios.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Accurate characterization of benign and cancerous breast tissues: Aspecific patient studies using piezoresistive microcantilevers

Abstract: Breast cancer is the largest detected cancer amongst women in the US. In this work, our team reports on the development of piezoresistive microcantilevers (PMCs) to investigate their potential use in the accurate detection and characterization of benign and diseased breast tissues by performing indentations on the micro-scale tissue specimens. The PMCs used in these experiments have been fabricated using laboratory-made silicon-on-insulator (SOI) substrate, which significantly reduces the fabrication costs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The results of those studies indicated that cancerous epithelial breast tissue specimens exhibited lower elasticity compared with benign samples, which was in accordance to the results obtained from tumor regions on needle biopsy specimens by Plodinec et al (2012). Recent investigations conducted by our group using piezoresistive measurements yielded similar observations (Pandya et al, 2014, 2015). …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of those studies indicated that cancerous epithelial breast tissue specimens exhibited lower elasticity compared with benign samples, which was in accordance to the results obtained from tumor regions on needle biopsy specimens by Plodinec et al (2012). Recent investigations conducted by our group using piezoresistive measurements yielded similar observations (Pandya et al, 2014, 2015). …”
Section: Introductionsupporting
confidence: 86%
“…Recent investigations conducted by our group using piezoresistive measurements yielded similar observations (Pandya et al, 2014(Pandya et al, , 2015.…”
Section: Introductionsupporting
confidence: 73%
“…Recently, much attention is focused on flexible, or skin-like sensor array with multiscale architectures for detecting mechanical, chemical, thermal, and optical changes [8-17]. The capability of analyzing and manipulating the biological materials at microscale and nanoscale and the possibility of incorporating it into portable lab-on-a-chip devices makes the MEMS sensor a potential candidate for diagnostic capabilities [18-26]. Each year in USA alone, more than 200,000 breast cancer cases are diagnosed [27].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive ductal carcinoma (IDC) and normal breast tissue specimens were carefully selected and extracted from Rutgers Cancer Institute of New Jersey Biospecimen Repository Shared Resource. Even though our specimens from a biobank went through preparation and preservation, our previous efforts showed the same trend of mechanical characteristics when compared with studies on fresh tissues from biopsy [27], [28]. Therefore, we chose to prototype and experiment with our new devices on banked human breast tissues which are easily accessible over fresh tissues.…”
Section: Methodsmentioning
confidence: 99%